La estructura ejemplar de la bioquímica - Lorenzano, César (Revista de Filosofía, 2007)
This article reconstructs biochemistry analyzing the structure of its exemplars. It is adequate to the expositive manners of scientists, and at the same time to scientific practice. It is a modified version of the structuralist approach, done without mathematical models. It conserves, however, its distinction between theoretical and no-theoretical terms, as well as the function of the paradigmatic exemplars in theory’s application. We propose a pragmatic empirical statement of biochemistry, introducing “a biochemical” as the epistemic individual that knows the structures of the theory, and uses them to find structural similarities between exemplars. We show in the historical analysis of the birth of biochemistry, that not only in its application, but its genesis we find the sequence of steps stated by the reconstruction. We propose that this reconstruction of a theory is appropriate to biological and biomedical knowledge, although it could be extended to theories of social or physical fields.